2022
DOI: 10.1177/11297298221100174
|View full text |Cite
|
Sign up to set email alerts
|

The positioning of the catheter tip with an intracavitary electrocardiogram in epicutaneo–caval catheter placement via lower limbs in newborns: A retrospective study

Abstract: Objective: Few studies have been conducted on whether catheterisation via the lower limb pathway is suitable for intracavitary electrocardiogram (ECG) technology. This study explored the positioning of the epicutaneo–caval catheter (ECC) tip with intracavitary ECG via the lower limbs in newborns to determine its optimal placement and to improve the success rate of ECC placement using this method. Methods: Twenty-eight cases were selected for the observation group. The tip location with intracavitary ECG method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…In recent years, IC-ECG has been widely used for locating the ECC tip, especially in neonates. Growing evidence suggests that IC-ECG is a safe, accurate, easy, and immediate approach for intraoperative ECC tip confirmation [ 6 , 8 , 10 , 11 , 14 , 16 18 , 20 ]. To our knowledge, this retrospective analysis is the first study to quantitatively describe the major changes in IC-ECG for ECC via the lower extremity and determine its effectiveness and safety, which extends upon previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, IC-ECG has been widely used for locating the ECC tip, especially in neonates. Growing evidence suggests that IC-ECG is a safe, accurate, easy, and immediate approach for intraoperative ECC tip confirmation [ 6 , 8 , 10 , 11 , 14 , 16 18 , 20 ]. To our knowledge, this retrospective analysis is the first study to quantitatively describe the major changes in IC-ECG for ECC via the lower extremity and determine its effectiveness and safety, which extends upon previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the ECC reference length was based on anatomical markers, while the actual insertion length was determined by IC-ECG, and the difference between the two was statistically significant ( P < 0.001). In neonates, increasing evidence has shown that IC-ECG-guided ECC placement can achieve more accurate tip positioning in the first attempt and reduce catheter-related complications [ 6 , 8 , 10 , 14 , 16 , 17 , 20 , 32 ]. Thus, it is necessary and valuable to use IC-ECG to locate the catheter tip during ECC catheterization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations